Comment « construire » une littérature nationale ? À propos des deux premières « Revue belge » (1830 et 1835-1843) - Lieven D’hulst (Contextes)
The construction of the Belgian nation from 1830 on makes a strong use of most cultural practices available, including literature. However, Belgian literature has to face at that time two major constraints: the need to subject itself to the larger cultural programs elaborated by national instances that hold back its autonomy at a moment when French literature tries to free itself of political meddlings; the need to supersede internal resistances, caused a.o. by language diversity, against a homogenous national literature. The article identifies and analyzes a number of construction procedures as they appear in two Belgian periodicals issued at the beginnings of the 1830s. More specifically, it concentrates on the most important discursive procedures, that make a dominant use of French models: procedures affecting enunciation, genre and language.